2009
DOI: 10.26719/2009.15.4.944
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a continuous care model on perceived quality of life of spouses of haemodialysis patients

Abstract: We carried out a semi-experimental study with simple randomized sampling to study the effects of applying a continuous care model on the quality of life of 36 spouses of haemodialysis patients in Hamedan, Islamic Republic of Iran. Participants took part in group discussions and training on the continuous care approach and completed the Perceived Quality Of Life (PQOL) questionnaire before and after the intervention. Mean scores on the physical, social and cognitive dimensions, as well as happiness and total sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 12 publications
2
27
1
1
Order By: Relevance
“…The CCM consists of four stages: (1) orientation, (2) sensitization, (3) control and (4) evaluation (14,15,17,18).…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CCM consists of four stages: (1) orientation, (2) sensitization, (3) control and (4) evaluation (14,15,17,18).…”
Section: Interventionmentioning
confidence: 99%
“…The main purpose of the CCM is to design a program that can effectively influence patients' attitude toward the disease, increase acceptance of treatment, and lead to proper performance for continuous care. This program is expected to be beneficial to control the disease and its potential complications (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…It was performed in 2016 in Baqiyatallah Allah (AS) hospital in Tehran. The sample size was calculated by using the standard deviation and mean value obtained from Rahimi's study (19). Considering a 20%, at least 32 patients were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…The chronic and weakening nature of disease, the long-lasting and dynamic therapy and patients' actual and potential problems (Rahimi et al, 2006) show their need to support (Tayyebi et al, 2010). The findings indicated that self-transcendence will effect increase of self-care and the life quality of chronic patients (Jadid-Milani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%